Changes in concentration performance and alternating attention after short-term virtual reality training in E-athletes: a pilot study - Maciej Lachowicz; Alina Żurek; Dariusz Jamro; Anna Serweta-Pawlik; Grzegorz Żurek (Scientific Reports, 2024)
Abstract In the dynamic landscape of e-sports, where intense competitive gaming demands high cognitive abilities, concentration performance and alternating attention play a pivotal role. E-sports encompass diverse genres, each requiring specific cognitive functions. Maintaining unwavering focus is crucial, as split-second decisions can determine victory. The study explores the potential of Virtual Reality (VR) training to enhance concentration performance and alternating attention, shedding light on the importance and possibilities of optimizing cognitive abilities for e-athletes. VR training emerges as a promising intervention, offering immersive environments for cognitive exercises. The study investigates the impact of VR training on concentration performance and alternating attention in amateur e-athletes, utilizing standardized tests. A randomized controlled trial with 66 participants reveals significant improvements in the VR training group, highlighting the adaptability and plasticity of cognitive processes. The findings suggest that VR training can enhance concentration abilities, providing valuable insights for e-sports and potentially extending to other fields requiring sustained attention and rapid task-switching. The study underscores the convergence of cognitive psychology, neuroscience, and VR technology, paving the way for innovative training methodologies and advancements in e-sports performance.